Brainchild Montpellier Danse Festival 2002 reviewed - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Premieres from Trisha Brown and John Jasperse Montpellier Danse 2002. PALABRAS CLAVE: Trisha Brown, John Jasperse, Montpellier Danse Festival, Giant Empty, Draw, Canto Piano, Twelve Ton Rose, Geometry of Quiet.